Teintures naturelles et teinturiers au Cambodge - Bernard Dupaigne (Revue d'ethnoécologie)
Based on the notes he has taken during his trips to many Cambodian villages in the late sixties, the author explains how villagers would use a traditional technique to dye skeins of silk threads, cotton and other fabrics in yellow, red, indigo, green and black. Most of the tints are obtained from plants. Red is the only one obtained from an animal product — exudate that comes from swarms of insect parasites kept on tree branches for this very purpose. Each tint holds detailed information about the collection of basic products, tints as well as additives (mordant), but also on how they made the tints and the various steps of the dyer’s work (measurements, times, etc.).